Multicenter Study of a Novel Topical Interleukin-1 Receptor Inhibitor, Isunakinra, in Subjects With Moderate to Severe Dry Eye Disease. Issue 5 (September 2017) - Goldstein, Michael H.; Martel, Joseph R.; Sall, Kenneth; Goldberg, Damien F.; Abrams, Marc; Rubin, Jay; Sheppard, John; Tauber, Joseph; Korenfeld, Michael; Agahigian, Jennifer; Durham, Todd A.; Furfine, Eric
Abstract : Objectives: Isunakinra, formerly known as EBI-005, is a novel interleukin (IL)-1 receptor inhibitor developed for topical treatment of patients with dry eye disease (DED). This phase 1b/2a multicenter, double-masked, randomized, vehicle controlled environmental trial assessed the safety and biological activity of isunakinra in patients with moderate to severe DED. METHODS: Subjects (N=74) were randomized to vehicle (placebo) or isunakinra (5 or 20 mg/mL) 3×/daily for 6 weeks. Evaluations included safety, tolerability, biological activity for signs (corneal fluorescein staining [CFS]), symptoms (pain or sore eyes and total Ocular Surface Disease Index [OSDI]), and reduction in rescue artificial tear use. Results: Topical administration of isunakinra (5 and 20 mg/mL) was safe and well tolerated and resulted in clinically relevant improvements in symptoms (OSDI score, painful/sore eye component of OSDI) and signs (total CFS) compared with baseline with no dose response. OSDI scores improved from baseline by 38% (18.9 points) at 6 weeks and CFS scores improved by 33% (3 points) in the isunakinra groups. These changes were not statistically significant compared with the vehicle. Use of artificial rescue tears was significantly reduced in the isunakinra treatment groups (mean=9 vials) compared with vehicle (mean=31 vials). The differences between isunakinra and vehicle treatments were more pronounced in subjects with OSDI scores less than 50 at baseline. Conclusions: Isunakinra was safe, well tolerated and showed clinically meaningful improvements in signs and symptoms of DED. These results encouraged the design of an adequately powered study to characterize the safety and efficacy of isunakinra in ocular surface diseases.